Strategi Pemasaran Minuman Gerai Sultan dalam Meningkatkan Minat Beli Konsumen di Sungai Pinyuh Kabupaten Mempawah - Satunnisa, Nia; Firayanti, Yuni; Marhamah, Marhamah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research discusses marketing strategies to increase consumer buying interest in Sultan Store drinks. The aim of this research is to find out marketing strategies to increase consumer interest in buying drinks at Sultan Stores. The research method used in this research is qualitative research. To obtain data in this research, the author used techniques including observation, in-depth interviews and documentation. The informants in this research were shop owners. The results of this research can be concluded that: Judging from the indicators of achieving marketing strategy objectives in increasing consumer interest in purchasing the Sultan's beverages, the way to increase consumer purchasing interest is marketing products via social media, such as Facebook, Instagram, etc. The way to promote the Sultan's drinks is by mouth to mouth. Judging from the indicators in improving the marketing of Sultan outlet stores, namely providing quality products, guaranteed to be safe and delicious. Because, Gerai Sultan Beverage Shop prioritizes its consumers to get the best products that are also safe to drink and also refreshing. Judging from the adaptation indicators, Toko Gerai Sultan has a very strategic location, because it is near the main road, namely Jl. Education, Sungai Pinyuh District, Mempawah Regency. This area is crowded with people and also school children, which allows it to attract many consumers to buy drinks at the Sultan Outlet Shop.